ANT POLLINATION OF AN INVASIVE NON-NATIVE WEED, EUPHORBIA GENICULATA ORTEGA IN NORTH WEST HIMALAYA (INDIA) (INDIA) - MOHD. ARAF; SATISH KUMAR; I. A. HAMAL (The Bioscan, 2009)
Euphorbia geniculata is an andromonoecious, self-compatible weed with higher seed set, viability and germination. The species is visited by hymenopterans, lepidopteron and dipterans. Out of hymenopterans, necterivorus ant (Camponotus compressus) comprised largest group (52.6 %). However at two study sites, it is exclusive visitor of the plant. Pollen exposed to ants revealed no significant reduction in viability. Seed set is limited by pollen availability, which is substantiated mainly by ants in this invasive weed.